Ketimpangan Pendapatan antara Wilayah Perkotaan dan Perdesaan di Indonesia tahun 2019-2023 - Rika Lusiana Simbolon; Timbang Sirait (Limits: Journal of Mathematics and Its Applications, 2025)
One of the biggest challenges in income inequality is the existence of income inequality between urban and rural areas, especially in developing countries. In 2019-2023, the average income of urban residents was 1.7 times higher than that of rural residents. The existence of income gaps between urban and rural areas can hinder equitable economic growth and worsen social inequality. Currently, household income is greatly influenced by the integration between the digital economy and the real economy. The development of the digital economy plays a role in increasing economic growth. However, its acceleration risks worsening social exclusion, inequality between groups, and wealth concentration. Therefore, this study aims to analyze the influence of the digital economy on income inequality between urban and rural areas in 33 provinces in Indonesia in 2019-2023 using a panel regression model. The results of measuring income inequality using the Theil L index show that the contribution of income inequality between urban and rural areas to national inequality has decreased in 2019-2023. The development of the digital economy in terms of infrastructure, business climate, research and innovation, and funding/investment has a significant influence in reducing income inequality between urban and rural areas. Meanwhile, in terms of human resources, it has a significant influence in increasing income inequality between urban and rural areas.